Over-the-counter medicines, economic conditions, and citizens most in need in Greece: Is it a challenge for primary care research? - Kamekis, Apostolos (Curr Pharm Teach Learn, 2020)
INTRODUCTION: Recent austerity experiences in Greece suggest a plausible link between extensive use of over-the-counter (OTC) medicines and socio-economic peculiarities of life. COMMENTARY: During the economic crisis in Greece, accessibility to healthcare services has been impacted, particularly for people with low income. However, this fact has not been systematically analyzed in conjunction with an observed increase in use of OTC medicines. Gaining a better understanding of the reasons leading to self-care may help to answer additional questions. Further research is needed to assess the gap between self-care and medically assisted care/treatment by designing pilot monitoring actions and focusing on behaviours related to OTC medicine use. Primary care can offer more collaboration between primary care physicians, community pharmacists, patients, and their families. IMPLICATIONS: It is crucial to create a multimodal research plan to gain a better understanding of motivational reasons that eventually lead to increasing use of OTC medicines. Efforts should be made to develop data collection techniques that will elicit information from various social groups that focus on changeable behaviours and perceived needs in relation to medicine consumption.